(untitled) (Eurasian Journal of History, Geography and Economics, 2022)
Many studies conducted in the world banking practice are aimed at determining the impact of competition on the banking sector and its level. In the research, there were two types of determining the level of competition: systemic and unsystematic. This article analyzes the opportunities for their use in the banking practice of the country by analyzing the strengths and weaknesses of various models of determining the level of competition in global banking practice